THE EFFECT OF WORK PERFORMANCE AND JOB PROMOTION ON EMPLOYEE WORK SPIRIT (CASE STUDY OF PT. INTERNUSA TRIBUANA CITRA MULTI FINANCE) - Ika Kartika; Vanessa Vicario (PT. MITRA ANGKASA INFORMATIKA, 2024)
Internusa Tribuana Citra Multifinance is a national scale company engaged in consumer finance. Declining employee performance can be seen from a lot of work that was not completed on time and the existence of work results that was blamed for resulting in the employer being disappointed and the work results of employees did not meet the standards of both quality and quantity of work. Job promotions are often ignored by superiors and decision-making for promotions of employees is less in reference to work evaluation. Decreased employee morale. The purpose of this study was to determine and analyze the effect of work performance and job promotions on employee morale at PT. Internusa Tribuana Citra Multifinance Regional Branch II. The population of this research is 40 employees of PT. Internusa Tribuana Citra Multifinance Regional Branch II. The sampling technique is done saturated sampling. The sample of this study also amounted to 40 employees of PT. Internusa Tribuana Citra Multifinance Regional Branch II. Data collection techniques used were: questionnaire, interview, document study and literature study. Analysis of the data used in this study is multiple linear regression analysis. The results showed that Job Performance and Job Promotion have simultaneous and partial effect on the morale of the employees of PT. Internusa Tribuana Citra Multifinance Regional Branch II. Keywords: Job Performance, Job Promotion and Work Spirit.